2002
DOI: 10.1177/009365002237833
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Heuristic-Systematic Model and Depth of Processing

Abstract: This study draws a nexus between heuristic-systematic information processing and the theory of planned behavior through a model of risk information seeking and processing. The model proposes that the form of information processing individuals apply to risk information from the media and other sources affects beliefs, evaluations, and attitudes considered important to making judgments about performing risk-reducing behaviors. This study found that deeper, more systematic processing of risk information is positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
167
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(180 citation statements)
references
References 36 publications
11
167
1
1
Order By: Relevance
“…To help validate the concept and measurement of systematic processing within the RISP model, and to examine the proposed relationship of processing to the structure of subsequent beliefs (Griffin et al, 1999), Griffin, Neuwirth, Giese, and Dunwoody (2002) examined the relationship between the RISP model and Ajzen's TPB. Consistent with RISP predictions, they found that systematic processing of risk information was positively related to attitude strength, evaluation strength, and the number of strongly held behavioral beliefs across three environmental risks and among residents of two metropolitan areas, results that are consistent with RISP model predictions based on Eagly and Chaiken (1993).…”
Section: [Insert Table 1 Here]mentioning
confidence: 99%
See 2 more Smart Citations
“…To help validate the concept and measurement of systematic processing within the RISP model, and to examine the proposed relationship of processing to the structure of subsequent beliefs (Griffin et al, 1999), Griffin, Neuwirth, Giese, and Dunwoody (2002) examined the relationship between the RISP model and Ajzen's TPB. Consistent with RISP predictions, they found that systematic processing of risk information was positively related to attitude strength, evaluation strength, and the number of strongly held behavioral beliefs across three environmental risks and among residents of two metropolitan areas, results that are consistent with RISP model predictions based on Eagly and Chaiken (1993).…”
Section: [Insert Table 1 Here]mentioning
confidence: 99%
“…10 Kahlor (2007) showed a positive zero-order relationship between worry and seeking. 11 Kahlor and Rosenthal (2009) Griffin et al (2002), however, found that channel beliefs related consistently to the apparent outcomes of processing, including the strength of cognitive structure regarding risk-related behaviors. 13 There is also some initial evidence that the communication-related variables in the RISP model might be applicable to individuals' seeking and processing of information about other issues, such…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The HSM assumes that people will engage in a systematic mode when they are not confident about the judgements they reach through the heuristic mode and when they want to maximise confidence in their judgement; in the literature this kind of motivation is called accuracy motivation (Chaiken 1980(Chaiken , 1987. Therefore, past research has shown that systematic processing of risk information may lead to more stable attitudes that are resistant to change (Griffin et al 2002;Yang et al 2010). …”
Section: The Heuristic-systematic Model and Its Relationship With Rismentioning
confidence: 99%
“…It was found that social norm and information seeking activities were most strongly related to information sharing. In the food domain the RISP-model has been tested on eating Great Lakes fish (Griffin, Neuwirth, Giese & Dunwoody, 2002;Griffin et al, 2004) examining the risks of eating poisoned fish and potential parasitic infection from drinking tap water. These studies, however, focused on information insufficiency and information processing behaviour, not on information sharing or seeking.…”
Section: Discussionmentioning
confidence: 99%